The first findings on rusty grain beetle, Cryptolestes ferrugineus (Stephens, 1831) (Coleoptera, Cucujoidea: Laemophloeidae) in pistachio orchard in Siirt province (Turkey) - Özgen, İnanç; Yücel, Abuzer; Karsavuran, Yusuf (My University, 2018)
In this study, Siirt province (Turkey) has been reported as the new distribution area for Rusty Grain Beetle, Cryptolestesferrugineus (Stephens, 1831). In addition, some morphological measures are presented. The measured length of thisspecies varies between 2.19 and 2.22 mm. It was found between May and June in pistachio orchards. In addition to beingfound in such pistachio areas, for this species; the facultative predator property must be observed. Adults as well aslarvae, are cannibalistic and will consume eggs, pupae and prepupae of other species co-habiting with them. For instance,It is important to monitor the relationship of this species with the species belonging to the family Scolytidae, Bostrichidaeand Diaspididae family species in this pistachio orchards in future.
Keywords: Biyoloji; Ziraat Mühendisliği; Entomoloji